(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2021)
This study purposed to evaluate the water quality of 10 points located between the Terelj national park and the Lun soum in Tuv province along the Tuul River, depending on assessing detailed Physico-chemical and seasonal (except than winter) pollution indicators. The chemical data of water samples from the Tuul River illustrated the water type from neutral to slightly alkaline and belonged to the HCO3– Ca2+; HCO3-, SO42–Na+ and HCO3– Ca2+, Mg2+. The point of Terelj or, moreover, starting points water belongs to excellent water, but water mineralization in the mid of Ulaanbaatar city increased up to 1.2 times. However, mineralization, anions and cations of T6 mixed with wastewater from the Central Wastewater Treatment Plant (CWTP) increased significantly. These parameters decreased along the downstream river at T9, T10 points in the zone of Lun soum. As nutritional polluting constituents like NH4-N, NO2-N, PO4-P, COD concentrations met the permissibility of National Standard (MNS 4586:98) requirements at T1-T5 points in Terelj and Ulaanbaatar city. On the contrary, ranges are overrated by permissible concentration of MNS 4586:98 at T6 point mixed with wastewater from CWTP. In T9, T10 points case, nutritional pollution is being decreased gradually along the river, but natural self-treatment did not process completely. Water quality index (WQI) of Terelj and mid of the city (T1-T5 points) designated as ‘excellent’ and ‘good’ (I-II), inappropriately at the point T6 appointed as ‘very poor’ to ‘unsuitable’ water (IV-V) categories. Interestingly, T7 to T10 issues contributed as ‘poor’ to ‘very poor’ water (III-IV) categories. Улаанбаатар хот орчмын Туул голын усны чанарын судалгаа Хураангуй: Туул голын урсгалын дагуу Тэрэлжээс Төв аймгийн Лүн сум хүртэлх 10 цэгээс улирал тутам дээж цуглуулан физик-химийн болон бохирдлын үзүүлэлтийг тодорхойлон, усны чанарын судалгааг явуулсаны үндсэн дээр бохирдлын түвшинг тогтоон дүгнэлт өгөх зорилгоор энэхүү ажлыг хийж гүйцэтгэсэн болно. Туул голын ус нь саармагаас бага шүлтлэг орчинтой, HCO3– Ca2+; HCO3-, SO42–Na+ ; HCO3– Ca2+, Mg2+. төрлийн холимог найрлагатай усны ангилалд хамаарагдаж байна. Голын эх буюу Тэрэлжийн бүс нэн цэнгэг усны ангилалд хамаарагдаж байсан бол Улаанбаатар хот орчмын бүсийн голын усны эрдэсжилт ойролцоогоор 1.2 дахин нэмэгдсэн байна. Харин Төв цэвэрлэх байгууламжийн хаягдал бохир ус нийлсэн (Биокомбинатын Т6) цэгт голын усны эрдэсжилт болон бусад анион катион ихээхэн нэмэгдэж байгаа боловч Лүнгийн бүсийн Т9, Т10 цэгт байгалийн усны өөрөө цэвэрших явцын дүнд нийт эрдэсжилт болон хатуулаг буурах зүй тогтол ажиглагдсан. Шим бохирдлын үзүүлэлт болох аммонийн азот, нитритийн азот, исэлдэх чанар, эрдэс фосфорын агуулга Тэрэлж, Улаанбаатар хотын бүсэд (T1-T5) цэгт стандартын утгаас хэтрээгүй байсан бол T6 цэгт огцом нэмэгдэж стандартын утгаас давсан байна. Харин Лүнгийн бүсийн Т9, Т10 цэгүүдийн хувьд шим бохирдлын үзүүлэлт урсгалын дагуу аажим буурч байгаа хэдий ч голын эхэн хэсэгтэй харьцуулахад гүйцэд цэвэрших процесс явагдаагүй нь харагдаж байна. Мөн Туул голын ус эхэн хэсэгтээ буюу Тэрэлж, Улаанбаатар хот орчмын бүсэд (T1-T5 цэг) “Маш цэврээс цэвэр” (I-II) усны ангилалд хамаарагдаж байсан бол Т6 цэгээс “Бохирдолтойгоос их бохирдолтой” буюу IV-V зэрэглэл рүү, харин Т7-Т10 цэгт усны чанар “Бохирдолтойгоос бага бохирдолтой” (III-IV) ангилал руу шилжиж буйг тогтоолоо. Түлхүүр үг: Туул гол, шим бохирдол, усны чанарын индекс, химийн найрлага